2012
DOI: 10.1007/s00595-012-0262-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of extrahepatic bile duct duplication with pancreaticobiliary maljunction and congenital biliary dilatation in children: a case report and literature review

Abstract: We herein report a case of cystic-type congenital biliary dilatation (CBD) in whom an extremely rare anomalous duplication of the common bile duct and pancreaticobiliary maljunction were diagnosed intraoperatively by meticulous surgical manipulations via conventional open surgery. By performing a dissection at the outer epicholedochal layer of the cyst, a thin cord-like structure shown to be the distal part of the common bile duct was identified. A further exploration revealed that the most distal (extra- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
0
9
0
2
Order By: Relevance
“…Several authors have reported cases of annular pancreas (AP), pancreas divisum (PD), and double common bile duct (DCBD) accompanied by PBM [34][35][36][37][38][39]. Our cohort included one patient with PBM and PD together without vascular variants.…”
Section: Discussionmentioning
confidence: 95%
“…Several authors have reported cases of annular pancreas (AP), pancreas divisum (PD), and double common bile duct (DCBD) accompanied by PBM [34][35][36][37][38][39]. Our cohort included one patient with PBM and PD together without vascular variants.…”
Section: Discussionmentioning
confidence: 95%
“…There are few reports of combined case of congenital choledocho-dilatation (choledochal cyst) with bile duct duplication [ 7 ]. In their report, all cases of choledoco-dilatation were cystic or fusiform type (Type I).…”
Section: Discussionmentioning
confidence: 99%
“…Boyden proposed that the development of type I DCBD was due to double vacuolization during the solid stage during the development of extrahepatic bile ducts, whereas chance elongation and early subdivision of the primitive hepatic furrow may be responsible for the other types of DCBD. [ 10 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] It is more commonly seen in children as it presents early in life due to abdominal pain and other associated symptoms. [ 10 ] Patients with ABPJ may invariably require surgery in the form of separation of the biliary and pancreatic systems to prevent the reflux of pancreatic juice as well as excision of the extrahepatic ducts, which are at risk of malignancy. It is important to know whether ABPJ is associated with the double common CBD.…”
Section: Discussionmentioning
confidence: 99%